Konflik Norma Antara UU No. 1 Tahun 2025 tentang Badan Usaha Milik Negara dan UU No. 17 Tahun 2003 tentang Keuangan Negara - Bayu Galang Saputra; Ahmad Sholikhin Ruslie (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The adoption of Law Number 1 of 2025, the third legislative modification to the regulations on State-Owned Enterprises previously governed by Law Number 19 of 2003, has resulted in a horizontal norm conflict with Law Number 17 of 2003 addressing State Finance. While Article 2 letter g of Law Number 17 of 2003 continues to classify segregated public assets placed in state-owned corporations as part of state finance, Article 4B of Law Number 1 of 2025 expressly states that losses sustained by public-Owned Enterprises do not represent state losses. The purpose of this study is to establish legally responsible ways for resolving the substantive conflict of norms between the two laws. This research adopts a normative juridical method, applying both the statutory approach and the conceptual approach. The theory of norm conflict resolution is operationalized as the primary analytical framework, while Gustav Radbruch's theory of the three fundamental values of law justice (Gerechtigkeit), legal certainty (Rechtssicherheit), and expediency (Zweckmässigkeit) serves as the analytical instrument used to examine the implications should this norm conflict remain unresolved. The findings indicate that this norm conflict cannot be mechanically resolved through the application of either the lex posteriori or lex specialis principles, as the two laws govern different dimensions of the same legal relationship. This contradiction generates a deficit across all three dimensions of legal value simultaneously, and has the potential to impede the prosecution of corruption offenses within State-Owned Enterprises while undermining the constitutional authority of the Supreme Audit Board (Badan Pemeriksa Keuangan). Comprehensive legislative harmonization and the filing of a judicial review petition with the Constitutional Court are identified as two resolution pathways that are legitimate within the hierarchy of laws and regulations.